Sustainable Agriculture: Case Study in Barebbo Village, Bone Regency - Andika Andika; Fitri Anugrah Sari; Rosida Salam; Siti Nurazizah Jufri; Ainim Paradita Paradita (Journal La Lifesci, 2020)
Ecological sustainability refers to the maintenance of the environmental order on earth so that its sustainability can be maintained. Three aspects must be considered to maintain the integrity of the environmental order, namely; carrying capacity, assimilative capacity and sustainable use of recoverable resources. Environmental development management is essential for ecosystem sustainability. Macroeconomic sustainability guarantees sustainable economic progress and encourages economic efficiency through structural and national reforms. Food security is defined as a condition for the fulfillment of food for households which is reflected in the availability of sufficient food, both in quantity and quality, safe, equitable, and affordable.